Coaches' role in shaping athletes' creativity in Pencak Silat: An Indonesian martial art study - Deny Saputro; Kurniati Rahayuni; Bayu Iswana; M. Fadli Dongoran; Yahya Eko Nopiyanto; Nagoor Meera Abdullah (Sriwijaya Journal of Sport, 2026)
Research Problems: Coaches play a crucial role in nurturing athletes' creativity, particularly in the context of Pencak Silat martial arts, which remains understudied. Research Objectives: Given the pivotal role of coaches in shaping athletes' creativity, this research seeks to examine how coaches can facilitate the development of creativity in Pencak Silat athletes, particularly in the sparring category. Methods: This study employed a qualitative method, with data collection conducted through semi-structured interviews involving four knowledgeable Pencak Silat experts as information sources. Results: The study findings demonstrate that the creativity of Pencak Silat athletes can be cultivated through the innovative resources provided by their coach. A key facet of coach creativity lies in their ability to adapt and evolve with changing times. Additionally, this research confirms that effective coaching involves providing athletes with a diverse array of tools while still allowing them the freedom to explore their problem-solving skills. Moreover, it underscores the importance of instilling creativity from an early age as a means of shaping the creativity of Pencak Silat athletes. Conclusion: This research leads to the conclusion that coaches stand as the most pivotal resource in fostering the creativity of Pencak Silat athletes. Achieving this entails designing training that encourages athletes to express their creativity, with the initiation of such simulations commencing from a young age.